PELATIHAN BAGI APARAT PEMERINTAH DESA, TEPATKAH DENGAN METODE PELATIHAN JARAK JAUH ? - A. Ali Mashduqi; Tohirin Tohirin (National Conference on Applied Business, Education, & Technology (NCABET), 2022)
This study aims to determine whether the distance training for village officials conducted by the Ministry of Finance in 2022 spread throughout Indonesia. The training carried out included village budgeting planning, village financial reporting and accountability, village asset administration and BUMDes Financial Management and Accountability. Data were collected through secondary data from RFTC Malang, RFTC Manado and RFTC Yogyakarta. In addition to secondary data, primary data was obtained from interviews with key informants, namely the training participants for village government officials. Data analysis was carried out qualitatively with processing stages in the form of transcription, reduction, categorization, and interpretation with reference to the research objectives. The results showed that the training participants felt that the training was very useful for them in supporting the implementation of their duties. In addition, the training is less effective if it is carried out with the full distance learning method. It is recommended that in the future the training is carried out in a "Blended" way, which is a combination of the Distance Training method and the Classical method